ADAM17 Genetic Variants and the Response of TNF-α Inhibitor in Rheumatoid Arthritis Patients - Kim HJ; Trinh NT; Choi Y; Kim W; Min KH; Kang SO; Kim JH; Kim HA; Jung JY; Choi IA; Lee KE (Dove Medical Press, 2020)
Hyun Jeong Kim, 1,* Nga Thi Trinh, 1,* Yunjeong Choi, 1 Woorim Kim, 1 Kyung Hyun Min, 1 Sang Oh Kang, 1 Joo Hee Kim, 2 Hyoun-Ah Kim, 3 Ju-Yang Jung, 3 In Ah Choi, 4 Kyung Eun Lee 1 1College of Pharmacy, Chungbuk National University, Cheongju-si, Republic of Korea; 2College of Pharmacy, Ajou University, Suwon, Republic of Korea; 3Department of Rheumatology, Ajou University School of Medicine, Suwon, Republic of Korea; 4Division of Rheumatology, Department of Internal Medicine, Chungbuk National University Hospital, Cheongju, Republic of Korea*These authors contributed equally to this workCorrespondence: Kyung Eun LeeCollege of Pharmacy, Chungbuk National University, 660-1 Yeonje-ri, Osong-eup, Heungdeok-gu, Cheongju-si 28160, Republic of KoreaTel +82 43 261 3590Fax +82 43 268 2732Email kaylee@cbnu.ac.krPurpose: TNF-α is a transmembrane protein which requires cleavage by ADAM17 in order to act systemically. The activation of ADAM17 to generate soluble TNF‑α results in an increased inflammatory activity. We hypothesized that variants spanning the ADAM17 gene contribute towards the observed variation in patient response defined by the number of changes in TNF‑α inhibitors.Patients and Methods: Seven single-nucleotide polymorphisms (SNPs) of ADAM17 in 63 patients with rheumatoid arthritis who received TNF-α inhibitors were analyzed: rs57467365, rs62117540, rs117645314, rs6432013, rs532704607, rs117179141, and rs12692386. Univariate and multivariate regression analysis were employed to investigate the independent predictable factors for changes in TNF-α inhibitors.Results: ADAM17 rs117645314 and rs117179141 showed significant association with the number of changes in TNF-α inhibitors. Patients with GA in rs117645314 and AT in rs117179141 had significantly higher chance of two or more changes of TNF-α inhibitors than those with wild homozygous alleles. Multivariate analysis showed that rs117179141 explained 5.7% of the 23.8% variability in TNF-α inhibitor response.Conclusion: This study showed that the number of changes in TNF-α inhibitor is associated with ADAM17 SNPs.Keywords: rheumatoid arthritis, TNF-α inhibitor, ADAM17, single-nucleotide polymorphism